Watershed Management: A Sustainable Strategy for Augmenting Water Resources and Mitigating Climate Changes - Lobo, Crispino (Annals of Arid Zone, 2016)
The relationship between environmental degradation, increasing rural poverty and climate change induced impacts has, in recent years, been increasingly dominating developmental and political discourse. Controversies apart, it is widely accepted that these three issues are intricately interwoven. Adverse changes in the one have a ratchet effect on the others. Of particular concern is that the already precarious existence of people living in ecologically fragile areas will be further jeopardized, in some cases, irretrievably. This paper outlines the case that in rain dependent rural areas, participatory environmental regeneration of living and livelihood spaces, along watershed lines, offers a promising way not only of building into the local economy a measure of resilience, but also of enhancing the productive capacities of natural resources.